Sleeve resection with end-to-end anastomosis in the reconstruction of tracheal defects exceeding six rings: a clinical feasibility study and safety assessment - Xia, Xin; Zhu, Xiaoli; Zhu, Yingying; Diao, Wenwen; Chen, Xingming (Frontiers in Surgery, 2024)
Objectives: Reconstruction is always required for tracheal defects and sleeve resection with end-to-end anastomosis is the most common used. The aim of the study was to present surgical techniques and evaluate the outcomes of sleeve resection with end-to-end anastomosis in the reconstruction of tracheal defects exceeding six rings. Methods: The study included patients with primary or secondary malignancies and tracheal stenosis from 2014 to 2019, who were treated with sleeve resection exceeding six tracheal rings, and reconstructed with end-to-end anastomosis. Airway status and patient outcomes were the principal follow-up measures. Results: A total of 16 patients were enrolled in the study including three primary tracheal malignancies, 12 invasive thyroid carcinomas and one with tracheal stenosis. The extent of tracheal resection ranged from seven to nine rings, and the primary end-to-end anastomosis was performed in all 16 patients. Performance of tracheostomy or cricothyroidotomy was done in six patients with extubation at a median of 42 days (range, 28-56). No anastomotic dehiscence, infection or bleeding occurred postoperatively, and all 16 patients maintained an unobstructed airway through the end of follow-up. Conclusions: Sleeve resection reconstructed with end-to-end anastomosis can serve as an appropriate therapeutic strategy for the tracheal defects even exceeding six rings. Adequate laryngeal release is the key to surgical success.